A solution for transmitting and displaying UHD 3D raw videos using lossless compression - Gomes, Ruan D.; Costa, Yuri G. G. da; A. Júnior, Lucenildo L.; Silva Neto, Manoel G. da; Duarte, Alexandre N.; Souza Filho, Guido L. de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
This paper describes a software-based approach for transmitting, and displaying ultra high definition (UHD) videos (ex: 4K) in raw format (2D or 3D).The viability of using lossless compression algorithms for transmission, and exhibition of UHD raw videos was investigated. This approach allows the transmission of raw videos for supporting the development of distributed edition tools for UHD videos, and high quality visualization using a lower bandwidth. We conducted performance studies of eight lossless compression algorithms, aiming at analyze the compression ratio for 4K videos, and the latency in video encoding and decoding. Finally, a multi-thread version of the LZ4HC was integrated with the Fogo Player, which is a software-based 4K player developed in a previous work. We obtained a reduction of about 38% in bandwidth requirements, and a decoding latency that allowed the exhibition in real time of 4K videos.